CHEMICAL CHARACTERISATION OF ACID MINE DRAINAGE AND ITS IMPACT ON SURFACE WATER QUALITY IN THE FORMER MINING AREA OF VALEA VINULUI (BISTRIȚA COUNTY – ROMANIA) - ROȘU, Cristina; ROBA, Carmen; VOICA, Cezara; BINDIU, Simina (Studia Universitatis Babeș-Bolyai Ambientum, 2018)
Acid mine drainage (AMD) represents a major source of environment pollution in both active and former mining areas. AMD have a high acidity and high levels of sulphate and toxic metals. The present study was focused on assessing the chemical caracterisation of AMD generated Gheorghiu gallery - Valea Vinului minining area and to evaluate the impact of AMD disposal onto surface water by calculating relevant water index. The AMD samples proved to be highly acidic (pH between 2.6 and 4.0) and contaminated with Zn, Cu, Al and Mn. The discharge of untreated acidic waters has a negative impact on Valea Băilor creek by increasing the content of Zn and Mn. The values of both HPI and MI confirm the negative impact of AMD discharge on the quality of surface water.